2008
DOI: 10.1590/s1677-54492008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Profilaxia da trombose venosa profunda: aplicação prática e conhecimento teórico em um hospital geral

Abstract: Background: Although this work belongs to the area of vascular surgery, it is relevant to all clinical and surgical specialties due to the clinical importance of deep venous thrombosis and its main complication, pulmonary embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 20 publications
(21 reference statements)
2
8
0
13
Order By: Relevance
“…The profile of the patients admitted, in terms of the proportions of clinical (62%) and surgical patients (38%), was no different to what has been observed at other general hospitals, 10,17 although patient risk stratification profiles do vary greatly at different institutions. Coexistence of several different guidelines, differences between patient profiles and, possibly, non-uniform analysis methods may be responsible for differences in the results reported by different authors.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The profile of the patients admitted, in terms of the proportions of clinical (62%) and surgical patients (38%), was no different to what has been observed at other general hospitals, 10,17 although patient risk stratification profiles do vary greatly at different institutions. Coexistence of several different guidelines, differences between patient profiles and, possibly, non-uniform analysis methods may be responsible for differences in the results reported by different authors.…”
Section: Discussionmentioning
confidence: 57%
“…[4][5][6][7][8][9] However, it has been observed that thromboprophylaxis prescription rates are low and, when thromboprophylaxis is administered, it tends to be incorrect, despite the fact that protocols are available to guide health professionals. 6,[10][11][12] This study was conducted to evaluate the VTE risk profiles of recently-admitted clinical and surgical patients and to assess the thromboprophylactic measures administered during the first 24 hours after admission.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is expected that this will lead to greater and more careful attention to this pathology by professionals and a reduction of thrombotic cases in outpatient units and hospitals. Pereira et al (2008) showed that only 38.46% of the physicians surveyed knew the incidence of DVT.…”
Section: Methods Of This Studymentioning
confidence: 99%
“…No estudo de Garcia e cols., de 182 pacientes que deveriam receber profilaxia medicamentosa para TVP, apenas 56 receberam a medicação 20 . Em outro estudo prospectivo, cujo objetivo foi verificar se a profilaxia medicamentosa estava sendo realizada de maneira rotineira e correta no Hospital Geral de Roraima, 100% dos pacientes da ortopedia não receberam profilaxia medicamentosa para TVP 14 .…”
Section: Tabela 02 Tipos De Fraturas Encontradosunclassified